Economic Prospects in the Context of Growing Regional Interdependencies: the European Union and the Eastern Partnership - Kharlamova, Ganna (Ekonomika, 2015)
The paper deals with the European Union programme devoted to the eastern neighboring states. Through its European Neighbourhood Policy (ENP), the EU works with its southern and eastern neighbours to achieve the closest possible political association and the greatest possible degree of economic integration. This goal builds on common interests and values — democracy, the rule of law, respect for human rights, and social cohesion. The EU is concerned that, despite sufficient funding and support from the EU, the targeted states did not raise to the EU targets for the programme or at least to a relevant one. We assume that such fact happened mostly because, although having very diverse economic and reform pasts emerged from the post-soviet period, they were considered and approached as a single group. The main hypothesis: has the umbrella of the EU funds in terms of the EaP provided for the six targeted states to intensify the growth of regional interdependencies as well as political cooperation and progressive economic integration? The main goal of the paper is to assess, by means of the statistical and comparison approach, the development and the economic sustainability of six targeted states (Belarus, Moldova, Ukraine, Armenia, Azerbaijan, and Georgia) in the period before and after the programme launching – the degree of regional interdependence and economic integration. The research was conducted using the methods of empirical (regression) analysis, theoretical explanations, descriptive analysis, and the Granger causality test.
Keywords: the EU; Easter Neighborhood Partnership; correlation; convergence; causality